THE INFLUENCE OF PRODUCTION PLANNING, INVENTORY CONTROL, PRODUCT QUALITY, AND COST EFFICIENCY ON THE OPERATIONAL PERFORMANCE OF MANUFACTURING COMPANIES - Maman Supriatman; Abu Naim; Agus Hermawan; Sapriyadi; Mardi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The manufacturing sector faces increasing pressure due to rising production costs, fluctuating demand, and intense global competition, forcing companies to improve operational performance to remain competitive and sustainable. Many manufacturing firms still experience inaccurate production planning, imbalanced inventory levels, inconsistent product quality, and inefficient cost management, resulting in delivery delays, high holding costs, product returns, and declining profitability. This study aims to analyze the influence of production planning, inventory control, product quality, and cost efficiency on the operational performance of manufacturing companies. A quantitative explanatory approach was employed using primary data collected from 200 managers and operational staff through structured questionnaires. The data were analyzed using Structural Equation Modeling (SEM) with AMOS to examine both simultaneous and partial effects. The results indicate that the research model demonstrates good goodness-of-fit and that all four variables have positive and significant effects on operational performance. Product quality shows the strongest influence, followed by production planning, cost efficiency, and inventory control. Together, these factors explain 72% of the variance in operational performance. The findings emphasize that integrating effective planning, inventory management, quality assurance, and cost control is essential for improving productivity, efficiency, competitiveness, and long-term sustainability in manufacturing organizations.